“Andarilhando pelas narrativas (auto)biográficas”: processos formativos de pesquisadoras em educação – Clio - Reis, Cristiane Medianeira da Silva (2020)
This Thesis was generated by the interest around the investigation about: To what extent is the Doctorate in Education process signified in the educational practices of PhDs and PhD students at the Center for Studies on Memory and Education - Clio? The general objective of the research is to analyze how the Doctorate in Education process is signified in the educational practices of PhDs and PhD students at the Center for Studies on Memory and Education - Clio. The consequences of this intention, in a specific way, are: To recognize in my (auto)biographical narrative senses and meanings in the formation trajectory and the encounter with the theme of this study; Map research in the area related to Thesis; Search for theoretical references on the continuing education of researchers in the field of education; Conduct a survey on the participants and research topics in monographs, dissertations and theses, as well as, predominant themes used by the Center for Studies on Memory and Education - Clio; To verify how the autobiographical narratives of doctors and doctoral students of the Center for Studies on Memory and Education - Clio narrate and interpret their formative processes and what they mean for educational practice. Qualitative research is presented as a methodology, using the method of (auto)biographical narratives, because it works the subject's personal and professional trajectory to the full, making it unveil about their formative experiences, allowing them to reflect and better understand how it means teaching practice. In this regard, it was verified with the researchers' narratives that the process of being a Ph. D. student in Education is daily meaningful by their educational practices in the classroom or by living some formative experience in which originated the research of their thesis. Thus, I perceive the power and relevance of the autobiographical narratives in the teacher's and professor's formation.